Parental Burnout: When Exhausted Mothers Open Up - Hubert, Sarah; Aujoulat, Isabelle (Frontiers in Psychology, 2018)
Until recently, research conducted on parental exhaustion was exclusively concerned with parents of sick children. However, situations where exhaustion occurs as a result of being physically and emotionally overwhelmed by one’s parental role in the absence of a child’s condition is gaining increasing interest. The aim of our study was to give voice to exhausted mothers, in order to get a better understanding of what it means to be exhausted in relation with one’s parental role, from the perspective of those who have experienced it. We referred to phenomenological interpretative analysis for methods of data collection and data analysis, and included 5 mothers who were each interviewed twice. Our analysis revealed a superordinate theme of fear, which was central in every aspect of the mothers’ accounts of their experiences, from the fear to not be a good enough mother to the fear related to unlearning control and experiencing discontinuity of one’s sense of self. Our results call for the development of specific interventions to prevent, anticipate or treat the phenomenon of exhaustion in parents, so as to help them and their children cope better with these situations of extreme vulnerability, which are often reinforced by senses of guilt, shame and loneliness.